The Position of Securities Crowdfunding is Reviewed from the Capital Market Definition Based on Law of the Republic of Indonesia Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector - Niken Previanti (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Crowdfunding has become one of the options for those who need funds to obtain funds from the wider community. Crowdfunding is funding a business, project, and so on that involves the community, usually done through internet networks. Crowdfunding is a technique for projects or business units involving the wider community. This study aims to determine the position of crowdfunding securities in terms of the definition of capital markets based on Indonesian Law Number 4 of 2023 concerning the development and strengthening of the financial sector. The research method used in this paper is the normative juridical legal research method, from Indonesian Law Number 4 of 2023 concerning the development and strengthening of the financial sector. The results of this study state that the position of Securities Crowdfunding in the capital market sector when viewed from the definition of the capital market in the PPSK Law still needs to be clarified. As an activity included in the capital market sector, Securities Crowdfunding activities should also be included in the definition of capital markets regulated in the PPSK Law.